Program Pelayanan Cetak Dokumen Langsung di Desa Rokan Koto Ruang Kabupaten Rokan Hulu: Sebuah Pendekatan Efektivitas - Wahyuni, Putri; Sihidi, Iradhad; Romadhan, Ach. Apriyanto (Indonesian Journal Publisher, 2025)
This study aims to analyze the effectiveness of the Pick Up the Ball program through the PECEL DESA innovation in Rokan Hulu Regency and to assess its impact on increasing ownership of population administration documents. The research employed a qualitative descriptive method, with data collected through interviews and documentation. Data analysis followed the stages of data reduction, data presentation, and drawing conclusions. The results show that the PECEL DESA program in Rokan Koto Ruang Village, Rokan Hulu Regency, has been effective in improving population administration services. Effectiveness is assessed using Riant Nugroho’s principles of accuracy: program, implementation, and target. In terms of program accuracy, PECEL DESA facilitated access for residents living far from the regency capital by simplifying the process of obtaining documents and reducing service time. Regarding implementation, the program was carried out in line with established Standard Operating Procedures (SOPs). In terms of target accuracy, the number of electronic ID card (e-KTP) holders increased significantly, reaching 98.12% of the village population. The study concludes that the PECEL DESA program is an effective innovation in strengthening village-level population administration services and can serve as a model for similar initiatives in other regions.